THE ROLE OF FREIGHT FORWARDERS IN IMPORT-EXPORT SERVICES(Case Study of PT. Sinotrans CSC Indonesia) - Kencana Verawati; Mohammad Naufal Abdullah, Arnold Habibie, Ziqra Maulana Zulmarjon, Sultan Sai’d Al Takhir Pasyah (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Logistics is a series of efforts that cover the effectiveness, planning, implementation, and supervision of a process of moving goods or services, energy, or other resources, from the starting point to the user point. Every company, in any form or field, especially in the field of commerce, cannot run properly to make a profit without the means of transportation (Hasibuan et al., 2021), This research method, some experts call it the positivistic method because it is based on the philosophy of positivism, Observation is a way to obtain information from an event through direct observation & Interview: a "systematic" method of obtaining information about subjects or "past, present and future events" in the form of "oral presentations". management of import documents using both FCL and LCL at PT Sinotrans CSC Indonesia, Ensuring that the goods arrive in good physical form to the Consignee's hands & Providing the best service and in accordance with the agreement with the Customer. Can understand the work process and scope of export and import activities, Know more clearly about what documents are needed or needed in the process of export and import activities & Know the obstacles and challenges experienced and must be faced while being a third party or liaison between Shipper and Consignee in the export and import process.